Viabilidad de las sociedades laborales en Ecuador. Una aproximación documental - Mercedes Montiel (Ius Humani. Jornal do direito, 2017)
Labour Societies have developed a particular interest in Spain, settling as corporations or limited liability companies, highlighting their characteristics that most of the capital is owned by the workers, who have a 51% stake in the capital, but with the limitations that each employee can not have more than one third of what makes up the capital and in the case of breaking the employment relationship, the worker must transfer their shares or participation to other partners for right of preference established in society, in order to maintain actions within it. For the above stated, the present work aims through a descriptive and documentary methodology with the technique of observation and document analysis, supported by triangulation and legal interpretation, analyze the structure of industrial societies, their benefits and limitations, to determine convenience and forecast the impact of the existence of labor Societies in Ecuador, proposing his alternative time about the various ways to guide and train workers and entrepreneurs for opening and participation in these businesses.